Biotransformation of Heavy Metals by Plant Growth Promoting Endophytic Bacteria: An Assessment - E. Mohana Priya; K. S. Tamilselvi (CV. Literasi Indonesia, 2023)
As a consequence of urbanization and industrialization, the environment is progressively polluted with heavy metals which is a problem of great concern. In plants it can create oxidative stress, ethylene production, chlorosis, Necrosis, stunted growth, inhibits various physiological processes, and decrease biomass. Due to their persistent and non-degradable nature, they enter the food chain leading to biomagnification and causing carcinogenic, mutagenic, and lethal effects on humans and animals. Bioremediation, phytoremediation, biotransformation, non-host inoculation, and other methods are used to treat heavy metals in the environment. Endophytic bacteria have gained attention for their potency to remove or immobilize heavy metals. Bacterial bioremediation is an effective and reliable technique to degrade, detoxify, mineralize, transform, or reduce the concentration of pollutants. This review helps in understanding the endophytic bacterial activity on bioremediation along with its plant growth-promoting properties.